Cardiovascular-kidney-metabolic comorbidities in colorectal cancer survivors: a nationwide cohort study on the role of metabolic syndrome - Liu, Xin; Zhao, Wenbo; Zheng, Chang (Frontiers in Endocrinology, 2025)
BackgroundColorectal cancer (CRC) survivors are at increased risk of cardiovascular-kidney-metabolic (CKM) complications. Although metabolic syndrome (MetS) is a recognized precursor of cardiovascular disease (CVD) in the general population, its prognostic relevance in CRC survivors has not been well established.MethodsWe retrospectively analyzed 32,740 patients with a history of CRC who underwent health check-ups recorded in a national hospital-based database between 2005 and 2021. MetS was defined according to the Chinese Diabetes Society (2017) criteria, requiring central obesity (waist circumference ≥90 cm in men or ≥85 cm in women) and at least two of the following components: elevated blood pressure, hypertriglyceridemia, low high-density lipoprotein cholesterol, or elevated fasting glucose. Patients were grouped by MetS status at baseline and followed for composite CVD outcomes, including myocardial infarction, angina pectoris, stroke, and heart failure.ResultsAmong 32,740 CRC survivors (median age 58 years; 65.2% male), 4,970 (15.2%) met the criteria for MetS. Over a mean follow-up of 945 ± 770 days, 2,137 composite CVD events occurred. Incidence rates were significantly higher in the MetS group than the non-MetS group (368.2 vs. 200.8 per 10,000 person-years). In multivariable Cox models, MetS was independently associated with elevated CVD risk (HR = 1.36, 95% CI: 1.20–1.54). The association remained significant in male participants (HR = 1.43, 95% CI: 1.24–1.64), but not in females (HR = 1.09, 95% CI: 0.87–1.36). Subgroup analyses revealed consistent associations across strata of age, treatment status, and cancer type, with stronger effects observed in patients without obesity (P for interaction < 0.05). Among individual MetS components, elevated blood pressure and fasting glucose showed the strongest associations with CVD outcomes.ConclusionsMetabolic syndrome is a significant predictor of cardiovascular events among colorectal cancer survivors in China.